Thesaurus Logistik: Eine neue Dimension des Terminologiemanagements - Petra, Keidel; Borchert, Friederike; Janiak, Tomasz (Glottodidactica, 2013)
The article aims to present the structure and key features of the internetbased bilingual(German and English) Thesaurus Logistics, developed by the Technical University of Applied Sciences Wildau in cooperation with the Institute of Shipping Economics and Logistics (ISL) and Institue of Logistics and Warehousing (ILiM). The comprehensive Thesaurus Logistics is based on the most advanced tools used for the developing of thesauri, namely: iQvoc and SKOS.